The long shadows of past insults: Intergenerational transmission of health over 130 years - Claudia Andreella; Martin Karlsson; Therese Nilsson; Matthias Westphal (Research Institute of Industrial Economics (IFN), 2016)
This paper investigates the intergenerational transmission of health in the very long run. Using a unique purpose-built administrative dataset on individuals born in Sweden between 1930-34 and their parents, we study the intergenerational transmission (IGT) of health and the impact of previous generations' health shocks on socioeconomic outcomes. Our results provide strong evidence in favour of IGT of health, in particular for males. In contrast to the existing literature that focuses on early life health outcomes, our paper shows that the effect on later-life mortality might be even more relevant. However, the story appears to be complex and multi-faceted: the IGT exhibits an inverted socioeconomic gradient, and the impact on socioeconomic outcomes is often very different from the effect on health.
Keywords: I12; J13; 330; Early environment; intergenerational transmission; Barker hypothesis; maternal health; infant health; socioeconomic status